Increased Detection of Pharyngeal and Rectal Gonorrhea in Men Who Have Sex With Men After Transition From Culture To Nucleic Acid Amplification Testing. Issue 2 (February 2017) - Cornelisse, Vincent J.; Chow, Eric P.F.; Huffam, Sarah; Fairley, Christopher K.; Bissessor, Melanie; De Petra, Vesna; Howden, Benjamin P.; Denham, Ian; Bradshaw, Catriona S.; Williamson, Deborah; Chen, Marcus Y.
Abstract : Background: This before-and-after study measured the impact of a change in testing methods from culture to nucleic acid amplification testing (NAAT) on the detection of pharyngeal and rectal gonorrhea in men who have sex with men (MSM) on a sexual health service level, including the effect on subgroups anticipated to have higher rates of gonorrhea. Methods: In March 2015, Melbourne Sexual Health Centre changed its laboratory method for gonococcal testing from culture to NAAT using the Aptima Combo 2 and Aptima GC tests. We compared the proportion of tests positive for rectal and pharyngeal gonorrhea in MSM using culture in 2014 with those using NAAT in 2015. Results: The proportion of tests positive for rectal gonorrhea by NAAT was double that obtained by culture (8% vs 3.9%; prevalence ratio [PR], 2.0; 95% confidence interval [CI], 1.8–2.4) and 5-fold for pharyngeal gonorrhea (8.3% vs 1.6%; PR, 5.2; 95% CI, 4.2–6.4). Similar increases in test positivity were observed in human immunodeficiency virus (HIV)-positive and HIV-negative men. By NAAT, test positivity for rectal gonorrhea was higher in HIV-positive compared with HIV-negative men (15.4% vs 7.3%; PR, 2.1; 95% CI, 1.7–2.6). Culture and NAAT had similar test positivity for rectal gonorrhea among men who reported contact with gonorrhea (24.9% vs 25.3%, PR 1.0, 95% CI 0.8–1.4) and men who presented with symptoms of proctitis (22.2% vs 27.9%, PR 1.3, 95% CI 0.8–2.0). Conclusions: A switch from culture to Aptima Combo 2 testing for extragenital gonorrhea in MSM increased detection and was most marked for pharyngeal infections. Abstract : A change in testing methods from culture to nucleic acid amplification testing resulted in a 2-fold and 5-fold increase in the detection of rectal and pharyngeal gonorrhea, respectively.